Elevator maintenance and performance in commercial building: Luxury hotel - Mustafa Kamal, Nik Khairul Azim; Abdul Tharim, Asniza Hamimi; Che Ahmad, Asmalia (2013)
Elevator is a vertical mechanical transportation in the multi storey buildings, which is important for the movement of people and goods quickly and safely.This movement should be quiet, trouble free and economical.The aim of this study focused on elevator maintenance and their performance.Hence, to achieve the aims, the objectives has been set which is to identify the frequency of the maintenance for elevator in luxury hotel building and to analysed the performance of elevator in luxury hotel building.To support this research, three (3) luxury hotel buildings located in Kota Bharu, Kelantan has been taken as a case study and the research methods cover through observation and semi-structure interview. Information about elevator maintenance and their performance was gathered through semi-structure interview with the hotel technician.The result from the survey indicates that the elevator maintenance and the elevator performance for this three (3) luxury hotel in Kota Bharu perform well.